Determinants of Conservation Agriculture for Sustainable Intensification (CASI) outscaling—a study in Coochbehar district of West Bengal, India - K K Das; Arunava Ghosh; P M Bhattacharya; T Dhar; A Chowdhury; M F Rola-Rubzen; M Gathala; T P Tiwari (Agricultural Economics Research Review, 2023)
The Sustainable and Resilient Farming Systems Intensification in the Eastern Gangetic Plains (SRFSI) project attempted to outscale Conservation Agriculture for Sustainable Intensification (CASI) practices in North Bengal. An exploratory study conducted during 2018–19 assessed adoption and the determinants of outscaling CASI. The SRFSI farmers allocated about 40% of their gross cropped area to CASI, and non-SRFSI farmers only 1%; both allocated more acreage in the winter. Adoption is influenced by proximity to resources, awareness of CASI, plot size, and women’s participation. To enhance adoption, mechanical hubs must be established near farms to provide the resources needed timely and effectively.